Building a Cocrystal by Using Supramolecular Synthons for Pressure‐Accelerated Heteromolecular Azide–Alkyne Cycloaddition. Issue 29 (11th April 2019) - Meng, Xiao; Chen, Changqing; Deng, Xinyuan; Wang, Zhangyuan; Chen, Qi; Ma, Yuguo
Abstract: Facilitated by the supramolecular synthons of carboxylic acids and amides through cooperative hydrogen‐bonding and arene–perfluoroarene interactions, the azide–alkyne cycloaddition reaction between two different molecules in a cocrystal was achieved. This reaction could be accelerated by pressure using a common hydraulic press equipment with excellent regioselectivity to yield 1, 4‐triazole products. The absence of decarboxylation side reactions in the products in the solid state demonstrated that this strategy can provide a green synthetic route for products not directly accessible by traditional syntheses in solution. Abstract : Engineering cocrystals : Facilitated by the supramolecular synthons of carboxylic acids and amides through cooperative hydrogen‐bonding and arene–perfluoroarene interactions, the azide–alkyne cycloaddition reaction between two different molecules in a cocrystal was achieved. This reaction could be accelerated by pressure using a common hydraulic press equipment with excellent regioselectivity to yield 1, 4‐triazole products.